2021
DOI: 10.3390/vaccines9040310
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Varicella-Zoster Virus Glycoprotein E Formulated with Lipid Nanoparticles and Nucleic Immunostimulators in Mice

Abstract: Theoretically, the subunit herpes zoster vaccine ShingrixTM could be used as a varicella vaccine that avoids the risk of developing shingles from vaccination, but bedside mixing strategies and the limited supply of the adjuvant component QS21 have made its application economically impracticable. With lipid nanoparticles (LNPs) that were approved by the FDA as vectors for severe acute respiratory syndrome coronavirus 2 vaccines, we designed a series of vaccines efficiently encapsulated with varicella-zoster vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 54 publications
4
20
0
Order By: Relevance
“…After the immunization schedule in Figure 3A, the Th2-oriented adjuvanted vaccines that were combined with Th1-skewing CpG ODN (including Poly I:C + CpG, cdi-AMP + CpG and Alum + CpG) all showed significant cellular immunity, which was shown by a higher proportion of IFN-γ-producing CD4 + T cells (Figure 4A) and IFNγ-producing CD8 + T cells (Figure 4B) compared with those of the sham controls. As a Th2-skewing adjuvant, poly I:C alone could induce not only potent humoral immunity, but also potent cellular immunity, which was confirmed in our previous studies [39]. For other Th2-skewing adjuvants that do not induce cellular immunity themselves, boosting immunization with Th1-skewing CpG ODN (shown as the immunization schedule in Figure 3D) could not induce cellular immunity, which was shown by the low proportion of IFN-γ-producing CD4 + T cells (Figure 4A) and IFN-γ-producing CD8 + T cells (Figure 4B) in the cdiAMP and Alum groups compared to the sham controls.…”
Section: Boosting Of Cpg Odn-adjuvanted Th1-oriented Subunit Vaccines Could Not Induce Cellular Immunity In Mice Primed With Alum-adjuvansupporting
confidence: 85%
See 1 more Smart Citation
“…After the immunization schedule in Figure 3A, the Th2-oriented adjuvanted vaccines that were combined with Th1-skewing CpG ODN (including Poly I:C + CpG, cdi-AMP + CpG and Alum + CpG) all showed significant cellular immunity, which was shown by a higher proportion of IFN-γ-producing CD4 + T cells (Figure 4A) and IFNγ-producing CD8 + T cells (Figure 4B) compared with those of the sham controls. As a Th2-skewing adjuvant, poly I:C alone could induce not only potent humoral immunity, but also potent cellular immunity, which was confirmed in our previous studies [39]. For other Th2-skewing adjuvants that do not induce cellular immunity themselves, boosting immunization with Th1-skewing CpG ODN (shown as the immunization schedule in Figure 3D) could not induce cellular immunity, which was shown by the low proportion of IFN-γ-producing CD4 + T cells (Figure 4A) and IFN-γ-producing CD8 + T cells (Figure 4B) in the cdiAMP and Alum groups compared to the sham controls.…”
Section: Boosting Of Cpg Odn-adjuvanted Th1-oriented Subunit Vaccines Could Not Induce Cellular Immunity In Mice Primed With Alum-adjuvansupporting
confidence: 85%
“…Among all of the adjuvants tested in this study, only CpG ODN induced Th1-oriented immune responses after vaccination, which implied successful cellular immunity production (Figure 1). While alum, cdiAMP, and poly I:C all induced Th2 responses, only poly I:C induced cellular immunity [31,39]. Interestingly, combination with CpG ODN reversed the alum-and cdiAMP-induced Th2 responses to the Th1 orientation, which was verified by both an antigen-specific IgG1-to-IgG2a antibody titer ratio lower than 1 (Figure 2) and production of antigen-specific IFN-γ-producing CD4 + /CD8 + T cells (Figure 4, including Poly I:C + CpG, cdiAMP + CpG and Alum + CpG).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most abundant glycoproteins with conserved neutralization epitopes and T cell epitopes, gE is essential for VZV replication and transmission between ganglia cells [24][25][26][27]43]. As a subunit antigen, the extracellular domain has shown potential as a safe varicella vaccine that could avoid the latency of viruses from live-attenuated vaccines, which may reactivate as herpes zoster, and has potential as a zoster vaccine with suitable adjuvants that induce powerful CMI [9,36,44,45]. Although the subunit vaccine Shingrix TM with the extracellular domain of gE adjuvanted with the AS01B system showed an excellent protection rate against herpes zoster, it was not reported for use as a safer varicella vaccine, mainly because of the limited supply and infeasible synthesis of the key components of AS01B, i.e., the polysaccharide mixture QS21, which is extracted from the bark of Quillaja saponaria, which is distributed in the temperate regions of South America [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…After linearization, T7 polymerase-mediated transcription was performed using an mRNA synthesis kit (APEXBIO Technology, Houston, TX, USA), and the product was purified with Monarch R RNA purification columns (NEW ENGLAND BioLabs Inc., Ipswich, MA, USA). LNP vaccines were prepared using a modified procedure previously described for mRNA vaccines [36][37][38]. Briefly, lipids (from AVT Pharmaceutical Technology Co., Ltd., Shanghai, China) were dissolved in ethanol at molar ratios of 50:10:37.5:2.5 (MC3: DSPC: cholesterol: DMG-PEG2000).…”
Section: Preparation Of Vaccinesmentioning
confidence: 99%
“…Likewise, Cao and Wang et al assessed the immune response to vaccines formulated with varicella zoster virus glycoprotein E with immunostimulatory nucleic acids in lipid nanoparticles (LNPs), all the components of which had been approved by the FDA in other vaccines. The mice immunized intramuscularly with LNPs responded with superior antibody- and cell-mediated immunity and antigen-specific virus-neutralizing antibodies relative to the mice immunized with alum [ 6 ]. The results suggested that LNPs may be a safe and economical potential varicella and zoster vaccine candidates.…”
mentioning
confidence: 99%